Risk factors of in-hospital mortality in patients with pneumocystis pneumonia diagnosed by metagenomics next-generation sequencing - Hou, Jun-Na; Liu, Heng-Dao; Tan, Qiu-Yue; Cao, Feng-An; Wang, Shi-Lei; Yao, Meng-Ying; Zhao, Yang-Chao (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: The metagenomic next-generation sequencing (mNGS) test is useful for rapid and accurate detection and identification of pathogenic microorganisms. The aim of the present study was to investigate the factors associated with in-hospital mortality in pneumocystis pneumonia (PCP) patients with mNGS-assisted diagnosis. Methods: Our study enrolled 154 patients with mNGS-positive PCP from August 2018 to February 2022 at the First Affiliated Hospital of Zhengzhou University respectively. Patients were divided into the survivor group (n=98) and the death group (n=56) according to whether in-hospital death occurred. Baseline characteristics, patients' pre-hospital symptoms and patients' CT imaging performance during hospitalisation were carefully compared between the two groups. Risk factors for the occurrence of in-hospital death were sought by selecting indicators that were significantly different between the two groups for modelling and performing multiple logistic regression analysis. Results: Compared with the in-hospital death patients, the survivors were younger and had higher levels of albumin (ALB) (age: 50.29±14.63 years vs 59.39±12.27 years, p<0.001; ALB: 32.24±5.62 g/L vs 29.34±5.42g/L, p=0.002; respectively), while the levels of lactate dehydrogenase (LDH) and C-reactive protein (CPR) were lower (LDH: 574.67±421.24 U/L vs 960.80±714.94 U/L, p=0.001; CRP: 54.97±55.92 mg/L vs 80.45±73.26 mg/L, p=0.018; respectively). Multiple logistic regression analysis revealed that age, the baseline LDH and CRP levels were all positively associated with high in-hospital mortality [age: OR(95%CI): 1.115 (1.062-1.172), p<0.001; LDH: OR(95%CI): 1.002 (1.001-1.003), p<0.001; CRP: OR(95%CI): 1.008 (1.000-1.017), p=0.045; respectively] while the platelet counts was negatively associated with it [OR(95%CI): 0.986 (0.979-0.992), p<0.001]. Conclusions: Old age, high baseline levels of LDH and CRP and low platelet counts were risk factors of the in-hospital mortality in mNGS positive PCP patients.